IMPLEMENTATION OF RT / RW NET HOTSPOT NETWORK WITH MIKROTIK-BASED VOUCHER SYSTEM AT UNITEX BOGOR HOUSING - Siregar, Martua Hami; Maisyaroh, Maisyaroh; Gunawan, Muhammad Fahri; Agustini, Fajar; Komarudin, Ishak (Journal of Information System, Informatics and Computing, 2023)
Technological developments are currently growing very rapidly, especially the use of computer networks. The use of the internet is increasing because it makes it easier for everyone to dig up existing information from the internet world, internet access has become a basic need for society. One effective way to provide internet access to the public is through the RT/RW Net network. However, there are still several obstacles in managing the RT/RW Net network in the Unitex housing complex in Bogor City, such as use that is not well controlled, many users who are not interested and do not have the right to use hotspot facilities by knowing the password for the Wi-Fi network in the housing complex. Unitex. To overcome these obstacles, the author proposes implementing an RT/RW Net network with a MikroTik-based voucher system. MikroTik is a network device that has reliable routing, switching and wireless capabilities. By utilizing MikroTik, RT/RW Net network managers can better manage and control internet access for users. By implementing the hotspot voucher login web page system provided by the Hotspot Server on the Mikrotik Router, to provide authentication features for users who will use the Hotspot/Wi-Fi network. So registered users are required to enter their username and password on the web login page provided by Mikrotik to be able to access the internet via the RT/RW Net Hotspot network. The research methods used in this research are observation, questionnaires, and literature studies, as well as the Network Development Life Cycle (NDLC) Method which is used to analyze needs in implementing the Rt/Rw Net Hotspot Network in the Unitex housing complex in the city of Bogor